Dietary Fibers: Effects, Underlying Mechanisms and Possible Role in Allergic Asthma Management - Roos E. M. Verstegen (MDPI AG, 2021)
The prevalence of asthma is increasing, but the cause remains under debate. Research currently focuses on environmental and dietary factors that may impact the gut-lung axis. Dietary fibers are considered to play a crucial role in supporting diversity and activity of the microbiome, as well as immune homeostasis in the gut and lung. This review discusses the current state of knowledge on how dietary fibers and their bacterial fermentation products may affect the pathophysiology of allergic asthma. Moreover, the impact of dietary fibers on early type 2 asthma management, as shown in both pre-clinical and clinical studies, is described. Short-chain fatty acids, fiber metabolites, modulate host immunity and might reduce the risk of allergic asthma development. Underlying mechanisms include G protein-coupled receptor activation and histone deacetylase inhibition. These results are supported by studies in mice, children and adults with allergic asthma. Fibers might also exert direct effects on the immune system via yet to be elucidated mechanisms. However, the effects of specific types of fiber, dosages, duration of treatment, and combination with probiotics, need to be explored. There is an urgent need to further valorize the potential of specific dietary fibers in prevention and treatment of allergic asthma by conducting more large-scale dietary intervention trials.